The Influence of Marketing Mix Variables on Consumer Decisions to Choose Panasonic Brand LED Television In Banda Aceh City - Jamil, Muhammad; Ismail (Indonesian Journal Economic Review (IJER), 2024)
This research is descriptive in nature, namely to reveal the problems that arise especially in the marketing world of electronic television products produced and marketed by PT. Panasonic Indonesia. The purpose of this study is to determine how much influence the marketing mix variable has on consumer decisions to choose Panasonic Brand Televisions in Banda Aceh City. The scope of this study is the field of marketing science that focuses on the marketing mix on consumer behavior in choosing products and the location of the research is in Banda Aceh City. The number of research samples was 100 people taken by Purposive Sampling. The results of the F Test (overall) show that the product factors (x1), price (x2), distribution (x3), Promotion (x4), together have a significant effect on the decision to purchase Panasonic products in Banda Aceh City, this can be seen from the F count of 31.511 and F table 2.467. This means that statistically it proves that the alternative hypothesis (Ha) proposed can be accepted and rejects the null hypothesis (Ho). While partially the price variable does not have a significant effect on the decision to purchase Panasonic products, while the product distribution and promotion variables have a significant effect on the decision to purchase Panasonic products in Banda Aceh City.